2020
DOI: 10.1177/1468798420938445
|View full text |Cite
|
Sign up to set email alerts
|

Use of touchscreen technology by 0–3-year-old children: Parents’ practices and perspectives in Norway, Portugal and Japan

Abstract: This paper discusses findings from online surveys completed by parents of 0–3-year-old children in Norway, Portugal and Japan concerning their young children’s use of touchscreen technology. The study investigated parental practices, views and perspectives related to children’s digital practices and explored these in relation to wider cultural discourses around early childhood in the participant countries. The study adopted Bronfenbrenner’s ecological systems theory to inform the questionnaire and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 37 publications
1
28
0
6
Order By: Relevance
“…Furthermore, these results are confirmed in other international studies, such as Dardanou et al ( 2020 ). In their study, Dardanou et al ( 2020 ) analyzed 0- to 3-year-olds children’s use of touchscreen devices at home in three different countries, Japan, Norway, and Portugal. The study results revealed that touchscreen technologies dominate in these three different countries.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Furthermore, these results are confirmed in other international studies, such as Dardanou et al ( 2020 ). In their study, Dardanou et al ( 2020 ) analyzed 0- to 3-year-olds children’s use of touchscreen devices at home in three different countries, Japan, Norway, and Portugal. The study results revealed that touchscreen technologies dominate in these three different countries.…”
Section: Discussionsupporting
confidence: 86%
“…Marsh et al ( 2015 ) reported that 0–5-year-olds had access to a tablet at home on an average of 79 min per day. In Japan, almost half the two-year-old children watched videos or played games through their parents’ smart screen devices for 60–80 min per day on average (Dardanou et al, 2020 ). Similarly, in the United States, children as young as four years of age spend an average of an hour per day on an interactive screen device (Rideout, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the sociodemographic factors which correlated with co-participation are likely to have a positive influence on the social and emotional components in the FEM and, thus, enable co-participation. For health promotion in practice, evidence-based guidance, such as guidelines on parental co-participation and on a daily balance between PA and DMU, is needed [ 21 ], as well as in parents’ views [ 98 ]. However, the findings reveal the need to take into account the sociodemographic differences that influence parents’ abilities and needs to co-participate.…”
Section: Discussionmentioning
confidence: 99%